A comprehensive assessment of mechanical and environmental properties of green concretes produced using recycled concrete aggregates and supplementary cementitious material - Ulucan, Muhammed; Alyamac, Kursat Esat (Springer Heidelberg, 2023)
This study aims to present a multi-perspective evaluation of green concretes produced using supplementary cementitious material and recycled concrete aggregates and to balance the reduction in compressive strength values caused by using recycled concrete aggregates with silica fume. For these purposes, statistical analyses were performed on the response surface method using the data of 9 reference and 27 green concrete series mixtures, and mathematical models were developed to predict the compressive strength with high accuracy. Then, energy consumption, global warming potential, and waste generation were taken into account from the environmental impact categories, and the environmental impact scores obtained were compared in detail to examine the impact of the use of silica fume and recycled concrete aggregates on sustainable development. Significant reductions in energy consumption and global warming potential values with the use of silica fume and waste generation values with the use of recycled concrete aggregates were achieved, and it was seen that supplementary cementitious material and recycled concrete aggregates are of great importance in terms of sustainable development. It was seen that these waste materials could be utilized, especially in regions with high earthquake risk, and that these waste materials are of great importance.
Keywords: Construction and demolition waste; Sustainable development; Recycled concrete aggregate; Supplementary cementitious material; Response surface method